Tanggung Jawab dan Sanksi Hukum bagi Pengemudi Tanpa Dilengkapi SIM - Alrasyid, Muhammad Saidi; Sujono , Sujono; Sudarto, Sudarto (Neolectura, 2025)
The high number of traffic violations is one of the causes of the high number of traffic accidents that occur, one of which is that drivers do not have a driving license. The police must take firm action against traffic violations and implement road traffic enforcement to minimize parties who commit traffic violations and to improve driving discipline in the community. Traffic police have an important role in traffic enforcement, by carrying out traffic tours, registration services and identification of motor vehicles or drivers, and traffic accident investigations. For that, it will be further studied how the legal responsibilities and sanctions for drivers without a driving license are based on Law Number 22 of 2009 concerning Traffic and Road Transportation and the role of the police in ensuring public compliance with the obligation to have a driving license for drivers. The research method used in this study is the normative legal research method. From the results of the study, it was found that the legal responsibilities and sanctions for drivers without a driving license are based on Law Number 22 of 2009 concerning Traffic and Road Transportation, the driving license also functions as a form of legal responsibility for drivers in maintaining their own safety and that of other road users. Drivers who do not have a driving license can be subject to criminal sanctions or fines as regulated in Article 281 of Law 22/2009, namely in the form of a maximum imprisonment of 4 months or a maximum fine of Rp1,000,000 and the role of the police in ensuring public compliance with the obligation to have a driving license for drivers, the Police, especially the traffic unit, continuously, both through preventive activities including guarding, regulating, patrolling and dikmas lantas activities in the form of counseling on traffic knowledge and activities in law enforcement in the form of taking action against traffic violators as an effort to foster a deterrent effect in committing traffic violations. From the results of the study for improvement, it is hoped that the Police must impose severe sanctions in addition to ticketing sanctions against drivers who do not have a driving license and the Government must form new legislation related to drivers who do not have a driving license in the Law, Legislation, government regulations, in order to provide certainty and legal benefits and law enforcement in driving on the highway.